Efeitos da violação espontânea de Lorentz na produção de ondas gravitacionais - Amarilo, Kevin Mota (2019)
In this work, we will present the effects of the spontaneous Lorentz symmetry breaking on the production of gravitational waves. First, we review some topics such as general relativity, Lorentz violation and gravitational waves. Then the equation of motion for graviton's field is modified by the presence of the bumblebee field. Using the Green's function method, we develop the solutions of the modified equation in the presence of external sources. Considering that the font has slow motion we derive a new quadrupole formula. Finally, we use the binary system in circular orbit problem to analyze the differences between the proposed model and the usual theory.